Endoscopic transorbital avenue to the skull base: Four-step conceptual analysis of the anatomic journey - Guizzardi, Giulia; Di Somma, Alberto; de Notaris, Matteo; Corrivetti, Francesco; Sánchez, Juan Carlos; Alobid, Isam; Ferres, Abel; Roldan, Pedro; Reyes, Luis; Enseñat, Joaquim; Prats-Galino, Alberto (Frontiers in Oncology, 2022)
Background In the last decades, skull base surgery had passed through an impressive evolution. The role of neuroanatomic research has been uppermost, and it has played a central role in the development of novel techniques directed to the skull base. Indeed, the deep and comprehensive study of skull base anatomy has been one of the keys of success of the endoscopic endonasal approach to the skull base. In the same way, dedicated efforts expended in the anatomic lab has been a powerful force for the growth of the endoscopic transorbital approach to the lateral skull base. Therefore, in this conceptual paper, the main steps for the anatomic description of the endoscopic transorbital approach to the skull base have been detailed. Methods The anatomic journey for the development of the endoscopic transorbital approach to the skull base has been analyzed, and four “conceptual” steps have been highlighted. Results As neurosurgeons, the eyeball has always represented a respectful area: to become familiar with this complex and delicate anatomy, we started by examining the orbital anatomy on a dry skull (step 1). Hence, step 1 is represented by a detailed bone study; step 2 is centered on cadaveric dissection; step 3 consists in 3D quantitative assessment of the novel endoscopic transorbital corridor; and finally, step 4 is the translation of the preclinical data in the real surgical scenario by means of dedicated surgical planning. Conclusions The conceptual analysis of the anatomic journey for the description of the endoscopic transorbital approach to the skull base resulted in four main methodological steps that should not be thought strictly consequential but rather interconnected. Indeed, such steps should evolve following the drives that can arise in each specific situation. In conclusion, the four-step anatomic rehearsal can be relevant for the description, diffusion, and development of a novel technique in order to facilitate the application of the endoscopic transorbital approach to the skull base in a real surgical scenario.